(untitled) (Herald of the National Children’s Medical Center, 2025)
With the development of neonatal cardiothoracic surgery in our country, perioperative care in pediatric cardiothoracic surgery is becoming increasingly important. One of the key aspects of a successful outcome of the intervention is the maintenance of optimal hemodynamic status through the use of various vasoactive and inotropic medications. This necessitates a deeper study of approaches to hemodynamic support in newborns during the early postoperative period.